A Wide-Beam Scanning Mode for Near-Space Passive SARs - Peng Zhou; Peng Ren; Yongshou Dai (International Journal of Antennas and Propagation)
A near-space passive SAR consists of a passive radar receiver placed on a near-space vehicle and another existing radar on a satellite serving as an illuminator. In this paper, we present a wide-beam scanning mode for near-space passive SARs for the purpose of increasing the azimuth scene extension. The receiving distance of a near-space SAR is much shorter than that of a satellite-based SAR, and the synthetic aperture time for a near-space passive SAR is not longer than the time interval during which a target transverses the azimuth beam of a transmitter. We design our novel mode by spreading the azimuth beam of a receiver to match the azimuth footprint of the transmitter. We also synchronize the azimuth beam of the receiver with that of the satellite within seconds during the beam scanning to further increase the scene extension. Furthermore, we formulate the azimuth scene extension and the footprint overlapping time for near-space passive SARs in terms of the possible locations of the involved satellites and receivers. Experimental simulations demonstrate the effectiveness of our proposed mode, especially revealing that the wide-beam scanning mode improves the azimuth scene extension and footprint overlapping time over the wide-beam mode, without decreasing azimuth resolution.